Enhance Teacher Competency Through Training in Compiling Mathematical Problems to Improve Students’ Critical Thinking Skills - Silwana, Amalia; Subaidah (Society : Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Critical thinking skill is one of the important skills that students must have in the 21st century learning. However, in reality, students’ critical thinking skills tend to be low because current learning does not involve it. Hence, teachers are expected to be able to compile mathematical problems that can improve students’ critical thinking skills. This community service project aims to provide teacher training in Roudlotul Mu’allimin Laban Menganti Gresik elementary school to compile mathematical problems that can improve students’ critical thinking skills as an effort to enhance teachers’ pedagogical competence. The method used in this community service project is Service Learning (SL) with three stages, such as planning, implementation, and evaluation. The results that have been achieved in the training implementation are that the teacher knowledge about how to compile mathematical problems to improve students’ critical thinking skills is increasing as evidenced by the difference between pre-test and post-test results. Before the training, there were no training participants who were able to compile mathematical problems that can improve students’ critical thinking skills. However, after the training, 77,78% of the training participants were able to compile it well.